GIS-based approach in land suitability evaluation for maize (Zea mays) and cassava (Manihot esculenta) production in Nsukka local government area of Enugu State - Chigozie Pascal Umeugokwe; Nancy Ekene Ebido; Ihuoma Eileen Uroawuchi; Chukwuebuka Edwin Awaogu; Obiageli Umeugochukwu; Chika Mike Jidere; Ifeyinwa Monica Uzoh; Charles Livinus Anija Asadu (Universitas Sebelas Maret, 2025)
Agriculture remains a cornerstone of economic development, food security, and the livelihoods of rural communities in sub-Saharan Africa. This study employed a parametric evaluation approach to assess the suitability of soils in the Nsukka Local Government Area (LGA) of Enugu State, Southeastern Nigeria, for cultivating maize (Zea mays) and Cassava (Manihot esculenta) using the Geographical Information System (GIS). The study applied the FAO land evaluation framework using systematic soil sampling, laboratory analyses, and GIS mapping. A total of thirty geo-referenced soil samples from the surface (0-20 cm) were gathered in triplicate across Nsukka LGA. Climatic and topographic data were integrated with soil parameters to assess suitability. Thematic maps were developed and overlaid to generate suitability classes for maize and cassava using the ArcGIS software. The climate characteristics were highly suitable for crop production. Topography (slope) and soil characteristics (texture, organic carbon, and base saturation) were the most limiting factors for both crops. The maps showed that 6.18% of the study region was highly suitable, while 93.82% was moderately suitable for maize production. The study region was entirely suitable for cassava cultivation. These results support the recommendation for crop-specific land-use planning and targeted soil management practices to improve maize productivity and leverage cassava's resilience in marginal soils.